2020
DOI: 10.1055/s-0040-1713163
|View full text |Cite
|
Sign up to set email alerts
|

Descrição do método de aferição dos parâmetros sacropélvicos para a inserção do parafuso S2-asa do ilíaco

Abstract: Resumo Objetivo Descrever como aferir os parâmetros sacropélvicos para a inserção segura do parafuso S2-asa do ilíaco (S2AI). Métodos Estudo descritivo do método de aferição dos parâmetros sacropélvicos para a inserção do parafuso S2AI por meio de tomografia computadorizada (TC). Os dados avaliados em reconstruções multiplanares foram os parâmetros da trajetória do parafuso, incluindo comprimento, diâmetro e ângulos de trajetória nos planos axial e sagital. Resultados A partir da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Accurate S2AI screw placement depended on proper trajectory angles in both sagittal plane and axial plane. Various recommended angles of trajectory had been reported by previous studies, ranging from 8.3°to 34.5°in the sagittal plane, and 32.1°to 42.5°in the axial plane, which made the spine surgeons confused [5,9,11,[17][18][19][20]. We thought that several factors might contribute to the variations of S2AI trajectory angles, such as etiology, race, the spatial position of the pelvis, and so on.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accurate S2AI screw placement depended on proper trajectory angles in both sagittal plane and axial plane. Various recommended angles of trajectory had been reported by previous studies, ranging from 8.3°to 34.5°in the sagittal plane, and 32.1°to 42.5°in the axial plane, which made the spine surgeons confused [5,9,11,[17][18][19][20]. We thought that several factors might contribute to the variations of S2AI trajectory angles, such as etiology, race, the spatial position of the pelvis, and so on.…”
Section: Discussionmentioning
confidence: 98%
“…Some scholars reported that free-hand technique was also reliable for S2AI screw placement in DLS patients, which obviated the need for intraoperative uoroscopy [5,[15][16]. However, the recommended ideal trajectory angles for S2AI screw placement varied in the literature [5,9,11,[17][18][19][20]. The S2AI screw traverse both the ilium and sacrum.…”
Section: Introductionmentioning
confidence: 99%
“…Various recommended angles of trajectory had been reported by previous studies, ranging from 8.3° to 34.5° in the sagittal plane, and 32.1° to 42.5° in the axial plane, which made the spine surgeons confused. 5 , 6 , 9 , 11 , 17 , 18 , 19 We thought that several factors might contribute to the variations of S2AI trajectory angles, such as etiology, race, the spatial position of the pelvis, and so on. The trajectory of S2AI screw goes through the sacrum, the sacroiliac joint space, and the ilium.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 15 , 16 However, the recommended ideal trajectory angles for S2AI screw placement varied in the literature. 5 , 6 , 9 , 11 , 17 , 18 , 19 The S2AI screw traverse both the ilium and sacrum. Therefore, there is no doubt that the S2AI screw trajectory is influenced by morphological characteristic of pelvis.…”
Section: Introductionmentioning
confidence: 99%